Construction of nano-heterojunction AgFeO2–ZnO for boosted photocatalytic performance and its antibacterial applications. (October 2021) - Janani, B.; Al-Kheraif, Abdulaziz A.; Thomas, Ajith M.; Syed, Asad; Elgorban, Abdallah M.; Raju, Lija L.; Das, Arunava; Khan, S. Sudheer
Abstract: The novel AgFeO2 –ZnO nano-photocatalyst with magnetic recyclability was prepared via facile sono-chemical route. HRTEM analysis showed intimate contact of AgFeO2 nanospheres on ZnO NPs. UV–vis-DRS verified excellent light harvesting capacity in visible-light region. XPS was used to verify chemical composition and valence states (Ag3d, Fe2p, O1s, and Zn2p). Peaks corresponding to tetrahedral/octahedral M−O bonds were noted in FTIR. The photocatalytic activity for dye degradation was boosted 10.5 times in AgFeO2 –ZnO nanocomposites (NCs) relative to pristine ZnO. The high surface area of NCs provided more reactive sites that enhance dye degradation. Trapping experiments indicated that h + and ·OH played a major role. The growth of Escherichia coli and Bacillus subtilis was inhibited to great extend on exposure with NCs. Hence, the investigation reports AgFeO2 –ZnO NCs can be used as an effective environmental remediation tool through photocatalysis and found to be active as a good antibacterial agent.